BRCA1 binds TERRA RNA and suppresses R-Loop-based telomeric DNA damage - Jekaterina Vohhodina (Nature Portfolio, 2021)
BRCA1-mediated resolution of R-loops has previously been described. Here the authors reveal a functional association of BRCA1 with TERRA RNA at telomeres, which develops in an R-loop-, and a cell cycle-dependent manner.